Impact of immersion and realism in driving simulator studies - Michael-Grigoriou, Despina; Kleanthous, Marios; Savva, Marinos; Christodoulou, Smaragda; Pampaka, Maria; Gregoriades, Andreas (My University, 2014)
Driving simulators emerged as a promising technology for the analysis of driving conditions and road users’ behaviour in an attempt to tackle the problem of road accidents. The work presented herein demonstrates the design and development of a driving simulator that aims to contribute towards evaluating black spots in road networks by promoting rapid design of realistic models and facilitating the specification of test scenarios. A reliable driving simulator should be able to reproduce the driver’s behaviour in a realistic way. In this study we examine different setups of the simulator to define the one that achieves highest levels of reliability. The chosen setup is then used to evaluate the impact of distractors (e.g. billboards) on driving behaviour of local road users for a chosen black spot in Limassol, Cyprus. Data collected from the experiments are analysed, and the main findings are presented and discussed.
Keywords: Driving simulator; Virtual reality; Computer graphics; Realism; Immersion; Driver’s behaviour; Driver’s distraction